The Influence of Social Focus Values on Performance and Competency: A Study on Select Organizations in Telangana State - Meesala, Appalayya; Vani, H.; Diana, Dolly (Prabandhan: Indian Journal of Management, 2015)
Human values held by an individual in the context of work that are (a) concerned with fellow human beings and (b) those concerned with perpetuity of organizations have to be studied for their impact on job performance and employee competency. Schwartz’s 10 basic values - self-direction, stimulation, hedonism, achievement, power, security, conformity, tradition, benevolence, and universalism- which are very general and relate primarily to a larger societal context, are not employee- or organization- focused. The last five values, namely, security, conformity, tradition, benevolence, and universalism - have little focus on human beings and are less encountered during work. The human values which are particular to the context of work (social focus values) are assumed to impact job performance and competency of employees. In view of scanty research into this aspect of employees and work in this part of the world, a research was undertaken with 144 employee respondents working in different organizations in and around Hyderabad. Path analysis was performed to unearth and measure the relationships between values and employee outcomes and the mediating role of competency. The model was also tested with AMOS software. The research shows that social focus values and organization perpetuity pursuit values impact performance only with the complete mediating role of competency. Contrary to popular view, these two values under examination have little direct effect on job performance, and competency alone predicts performance, and not social focus and perpetuity pursuit values.